Investigation into percolation and liquid water content in a multi-layered snow model for wet snow instabilities in Glacier National Park, Canada - Madore, J-B.; Fierz, C.; Langlois, A. (Frontiers in Earth Science, 2022)
Water percolation in snow plays a crucial role in avalanche risk assessment. Liquid water content and wetting front are hard to measure on the field, thus good simulation of the phenomena can be of great help for forecasters. This study evaluates water percolation simulations with the SNOWPACK model using the Richards scheme on mount Fidelity, Glacier Nation Park, Canada. Emphasis was put on the quality of the input data and parameters. The analysis of the precipitation phase temperature threshold showed that a value of 1.4°C was best suited to track the rain/snow transition on site. A 10-year analysis of 24h precipitation measured by the rain gauge and 24h new snow water equivalent showed an excellent correlation. New snow density sub-models were evaluated using the 24h new snow density taken by the park technicians. The BELLAIRE model performed best and was used to drive the snow simulations. The two SNOWPACK snow simulations were evaluated using rain gauge precipitation amount and automatic snow height measurement at the same site. Both runs simulated the main snowpack layers observed during the dry season (i.e. before spring percolation was observed) and both simulated the snow properties with good accuracy. Snow water equivalent generated by both simulations was slightly underestimated compared with four manual measurements taken on-site during the winter. Nevertheless, the comparison of both measured and modelled bulk density showed great correspondence. The evaluation percolation timing and wetting front depth were evaluated using field measurements and on-site instruments. Main percolation events were correctly simulated as well as timing with avalanche cycle. The results suggest that the use of optimal input data led to a valid simulation of the waterfront and percolation timing on a new site. Good percolation information generated with the SNOWPACK model and Richards scheme could be used to assess snowpack stability by forecasters in areas where such data are available.